Pemilihan Karyawan Tetap PT. Jawasurya Kencana Indah menggunakan Metode Moora - Putriniantami, Bertha Sonia; Daru, April Firman (Syntax Literate, 2025)
Jawasurya Kencanaindah faces challenges in determining contract employees who are worthy of being appointed as permanent employees, considering that the selection process is carried out manually and is less objective. This study aims to apply the Multi-Objective Optimization by Ratio Analysis (MOORA) method in the Decision Support System (SPK) to improve efficiency and objectivity in the selection of permanent employees. The research method involves several stages, including problem analysis, literature study, application of the MOORA method, calculation of alternative values based on predetermined criteria, and evaluation of results to determine the best employees. The criteria used in the selection include work assessment, attendance, competence, tenure, and integrity and work ethics. The results of the study show that the MOORA method is able to optimize employee selection by considering various factors simultaneously. The alternative with the highest score is identified as the best candidate to be appointed as a permanent employee. With this approach, the selection process becomes more transparent, fast, and accurate. In conclusion, the use of the MOORA method in SPK has succeeded in increasing the effectiveness of the selection of permanent employees at PT. Jawasurya Kencanaindah. The implication of this study is that companies can adopt this method to reduce subjectivity in decision-making as well as increase employee satisfaction and motivation through a fairer and more structured selection system.